Health Coaching to Improve Mother’s Self Efficacy in the Implementation of Prevention Malnutrition in Children - Yuni Sufyanti Arief (Journal of Global Pharma Technology, 2020)
Introduction. One of the factors causing nutritional problems that can be modified and has an influence on the nutritional status of children under five is the pattern of parenting or child care by the mother, because the mother is a personal preference in fulfilling family nutrition. The family will play an important role in preventing nutritional deficiencies in each member of the family. The purpose of this study was to examine the effect of health coaching on maternal self-efficacy in preventing malnutrition. Method. Quasy-experimental design with pre-post control group was used as a method in this study. A total of 30 parents were used as respondents, divided into 15 for the treatment group and 15 for the control group. The sampling method used was purposive sampling based on inclusion criteria. Self-efficacy as the dependent variable and health coaching as the independent variable. The data were collected by means of a questionnaire and analyzed using the Wilcoxon rank sign test and the Mann Whitney U test with a significance level of ≤ 0.05. Results. The results showed the wilcoxon results for the treatment group p 0.008, the control group showed a p score of 1,000. Mann Whitney test showed a p score of 0.003. Conclusion. Health coaching is effective in increasing maternal self-efficacy in preventing malnutrition. The mechanism of change is by changing the Health inhibiting Thinking (HIT) in the mother to become Health enhancement Thinking (HET). The results of this study can be used as an alternative health promotion method.